Allergic diseases aggravate the symptoms of SARS-CoV-2 infection in China - Zhang, Huishan; Lin, Jilei; Wu, Jinhong; Zhang, Jing; Zhang, Lei; Yuan, Shuhua; Chen, Jiande; Tang, Qiuyu; Zhang, Ailian; Cui, Yuxia; Xu, Xiaojuan; Dai, Hongxie; et al. (Frontiers in Immunology, 2023)
The relationship between allergic diseases and the adverse outcomes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been a subject of controversy. This study aimed to investigate the association between allergic diseases and the incidence and severity of symptoms in SARS-CoV-2 infection. Methods: Clinical data of individuals, including children and their parents, infected with SARS-CoV-2 from December 2022 to January 2023 in China were retrospectively analyzed. The data were collected through questionnaires. Statistical analysis, including chi-squared tests, nonparametric analysis, one-way ANOVA, and logistic regression analysis, was used to examine the relationship between allergic diseases, prior medication, and the symptoms of SARS-CoV-2 infection. Results: There were 3,517 adults and 3,372 children with SARS-CoV-2 infection included in the study. Fever was found to occur at similar rates in children (86.5%) and adults (86.8%). However, other symptoms related to respiratory issues (such as cough and sore throat), neurological symptoms (headache, loss of smell, and loss of taste), and systemic symptoms (muscle soreness and weakness) were observed more frequently in adults (P < 0.001).Additionally, adults exhibited higher overall symptom scores, indicating greater severity. Allergic diseases were found to be associated with the incidence of certain SARS-CoV-2 infection symptoms in both children and adults. Specifically, children with allergic rhinitis (AR) were observed to be more susceptible to upper respiratory symptoms (OR: 1.320, 95% CI: 1.081-1.611, P = 0.006), while asthma patients were found to be more susceptible to severe respiratory symptoms (OR: 1.736, 95% CI: 1.250-2.411, P = 0.001). Similar patterns were identified in adults. Furthermore, AR was also suggested to be a risk factor for symptom severity in both children (OR: 1.704, 95% CI: 1.314-2.209, P < 0.001) and adults (OR: 1.736, 95% CI: 1.250-2.411, P = 0.001). However, prior medication for allergic diseases did not exhibit a preventive effect on SARS-CoV-2 infection symptoms.Conclusions: Both children and adults with allergic diseases were found to be more prone to experiencing symptoms of SARS-CoV-2 infection, and these symptoms tended to be more severe.